Two years between life and death: A critical analysis of the suspended death penalty in China. (June 2016) - Miao, Michelle
Abstract: The suspended death sentence is a unique form of penal punishment in the Chinese criminal regime. In the context of the recent death penalty reform, an increasing resort to the suspended death penalty has been acclaimed to facilitate a substantial reduction in the use of the death sentences and executions. While most academic attention has been paid to its utility as an alternative to the death penalty, little is devoted to examining its penological grounds and practical use. This article seeks to fill this gap by describing the unduly complicated penal landscapes and discussing problematic consequences concerning the use of the suspended death penalty in contemporary China. It investigates its ambiguous nature, fuzzy boundaries and problematic implementation processes. It is the hope that the article will inspire further empirical exploration on this topic of great theoretical and policy import.